Differences in the Effect of Chair Based Exercise and Otago Exercise on Balance Disorders in the Elderly at Posyandu Dewi Sartika Sidoarum - Aprianda, Anisa; Muhammad Ali Jafar; Tyas Sari Ratna Ningrum (Jurnal Kesehatan Cendikia Jenius, 2025)
Background: In the elderly there are changes in the biological and psychological functions of the elderly, which usually worsen, giving rise to problems including those within themselves such as sensory, cognitive, central nervous system and musculoskeletal disorders which cause a decrease in balance, resulting in balance disorders and decreased muscle strength. , and muscle flexibility decreases. Objective: The aim of this study is to determine the difference in the effect of providing Chair Based Exercise and Otago Exercise on improving balance in the elderly. Method: This study used quasi experimental with pre test and post test two group design, total sample 26 divided into 2 groups. Group I was treated with Chair Based Exercise and Group II was treated with Otago Exercise. This research was conducted for 4 weeks with 3x training per week. Results: Testing hypothesis I using the Wilcoxon Test showed a value of p0<001 (p0<05) the results of testing hypothesis II using the Wilcoxon Test revealed a value of p0<001 (p0<05) which means that the two treatments had an influence on improving the balance of the elderly. The results of hypothesis III using Mann-Whitney showed that the value in groups I and II was p=0.383 (p>0.05), which means there was no difference between the two exercises. Conclusion: There was no difference in the effect of providing Chair Based Exercise and Otago Exercise on improving balance in the elderly. Suggestion: Future researchers can use the same method with broader data characteristics and a larger number of samples.